EU ETS impact on companies’ performance in Portugal: a sector analysis - Madaleno, M.; Alves, M. R.; Meireles, M.; Silva, Pablo (7th APEEN Conference / Energy Economics International Conference, 2023)
The main goal of this study is to evaluate the influence of the European Union Emissions Trading System (EU ETS) on the Financial Performance of Portuguese firms and to assess its effectiveness in changing firms’ environmental behavior. Empirically, it intends to test how Portuguese companies are financially impacted by the EU ETS system and its allowances market. To this end, it was initially estimated a simple panel model for the period between 2012 and 2020 for the Portuguese companies using European Commission's and SABI´s (Iberian Balance Sheet Analysis System) database. Afterward, a generalized method of moments (GMM) estimations was performed. From the results, it was possible to observe that the impact of EU ETS is limited, albeit with a negative effect on the profitability of companies, as it tends to reduce emissions, and these are positively related to the firm’s profits. Furthermore, the results show evidence that technology policy has become an important part of the policy portfolio that complements climate policy. Based on these findings, the paper provides some advice for policymakers on how to improve the existing policy portfolio.